Religious studies beyond the discipline: on the future of a humanities Ph. D. - McCutcheon, Russell T. (NAASR working papers, 2024)
"The aim for the volume is to initiate and then move forward a conversation among future, current, and recent graduate students as well as those who train them concerning the content, process, and purpose of acquiring advanced research skills in the early twenty-first century university"--